Eco-archaeological excavation techniques reveal snapshots of subterranean truffle growth - Büntgen, Ulf; Peter, Martina; Tegel, Willy; Stobbe, Ulrich; Elburg, Rengert; Sproll, Ludger; Molinier, Virginie; Čejka, Tomáš; Isaac, Elizabeth L; Egli, Simon (Fungal biology, 2021)
Despite its status as a highly-prized and coveted fungi in gastronomy, many aspects of the subterranean life cycle of the Burgundy truffle (Tuber aestivum) are still unknown, because in situ observations of the formation and maturation of truffle fruitbodies remain difficult. Here, we adopted a suite of archaeological fine-scale excavating techniques to provide unique spatiotemporal snapshots of Burgundy truffle growth at three sites in southern Germany. We also recorded the relative position, fresh weight, maturity level and genotype composition of all excavated fruitbodies. Varying by a factor of thousand, the fresh weight of 73 truffle ranged from 0.1 to 103.2 g, with individual maturity levels likely representing different life cycle stages from completely unripe to fully ripe and even decaying. While only a slightly positive relationship between fruitbody weight and maturity level was found, our results suggest that genetically distinct specimens can exhibit different life cycle stages at the same period of time and under the same environmental conditions. We therefore argue that truffles are likely able to grow, mature and ripe simultaneously between early summer and late winter of the following year. Our case study should encourage further eco-archaeological truffle excavations under different biogeographic settings and at different seasons of the year to gain deeper insights into the fungi's subterranean ecology. The expected cross-disciplinary findings will help truffle hunters and farmers to improve their harvest practices and management strategies.
Keywords: Archaeological excavation; mykorhiza; Mycorrhizae; Germany; Seasons; Fungal phenology; Truffle ecology; Tuber aestivum; Německo; Gourmet food; roční období; Fruitbody formation